Features of Organizational and Technical Measures to Increase the Level of Survivability and Explosion and Fire Safety of Potentially Dangerous Objects - Onishchenko, V. V.; Sukhai, S. M. (Science and Transport Progress, 2024)
Purpose. The work is aimed at studying the peculiarities of organizational and technical measures to improve the level of explosion and fire safety of potentially dangerous objects. Methodology. To achieve this goal: 1) a study was conducted to identify possible hazards and risks at potentially hazardous facilities; 2) practical organizational and technical measures to improve the level of explosion and fire safety of hazardous facilities were analyzed; 3) the composition and capabilities of the system of early detection of the threat of emergencies and warning, as well as the possibility of implementing this system at the relevant facilities of the Armed Forces of Ukraine were assessed; 4) the main types of automated warning and the principles of their operation were considered, and the available technical solutions were analyzed. Findings. The peculiarities of organizational and technical measures to improve the level of explosion and fire safety of munitions storage facilities are summarized. The key stages of the implementation of technological solutions to ensure the survivability of potentially hazardous facilities are identified. Originality. For the first time, an analytical justification for the need to use hazard monitoring systems and timely warning of possible emergencies at munitions storage facilities and other potentially hazardous facilities was carried out. The features of design and technological solutions to improve the level of explosion and fire safety of munitions storage facilities through organizational and technical measures are considered. Practical value. The implementation of effective design and technological solutions for the use of hazard monitoring systems and timely warning of possible emergencies will allow to move from damage localization measures to the forecast and prevention of disasters and reliable protection of munitions storage facilities of the Armed Forces of Ukraine, other potentially dangerous facilities and critical infrastructure of the state.